2017
DOI: 10.1155/2017/7094781
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Machinery of Young and Senescent Human Umbilical Vein Endothelial Cells and Their Microvesicles

Abstract: We examine the antioxidant role of young and senescent human umbilical vein endothelial cells (HUVECs) and their microvesicles (MVs). Proteomic and Western blot studies have shown young HUVECs to have a complete and well-developed antioxidant system. Their MVs also contain antioxidant molecules, though of a smaller and more specific range, specialized in the degradation of hydrogen peroxide and the superoxide anion via the thioredoxin-peroxiredoxin system. Senescence was shown to be associated with a large inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 72 publications
1
21
0
4
Order By: Relevance
“…In a recent work, we demonstrated the existence of a functional machinery for ROS detoxification in HUVEC eMVs [ 27 ]; now, our present study demonstrates that these HUVEC eMVs, especially those derived from senescent cells, can synthesize NAD(P)H, the fuel that feeds the antioxidant machinery, used as precursors of different blood plasma metabolites. The combination of both results indicates that eMVs are subcellular structures with an autonomous capacity for ROS scavenging, as had been suggested by Soleti et al [ 31 ]; eMV protection against oxidative stress regulating eNOS/Akt signaling has also been recently demonstrated [ 32 ].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In a recent work, we demonstrated the existence of a functional machinery for ROS detoxification in HUVEC eMVs [ 27 ]; now, our present study demonstrates that these HUVEC eMVs, especially those derived from senescent cells, can synthesize NAD(P)H, the fuel that feeds the antioxidant machinery, used as precursors of different blood plasma metabolites. The combination of both results indicates that eMVs are subcellular structures with an autonomous capacity for ROS scavenging, as had been suggested by Soleti et al [ 31 ]; eMV protection against oxidative stress regulating eNOS/Akt signaling has also been recently demonstrated [ 32 ].…”
Section: Discussionsupporting
confidence: 64%
“…The contribution of ROS to aging has been widely documented, although the beneficial effects produced by ROS have led to a new interpretation of this traditional view [ 57 59 ]. An increase of ROS production has also been related with senescence, an experimental model widely used in aging studies [ 20 , 24 , 60 ] and also demonstrated in our previous work in senescent endothelial cells [ 27 ]. In accordance with the stronger capacity of ROS elimination demonstrated by senescent eMVs in our previous work, the present study demonstrates a strong increase of the machinery involved in NADPH synthesis in senescent eMVs.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…EVs are essential modulators of vascular cell functions relevant to vascular inflammation and atherosclerosis [126,127]. Furthermore, EVs have been identified as cell-to-cell communicators.…”
Section: Hif and Atherosclerosismentioning
confidence: 99%